Assessment of left ventricular diastolic function with cardiovascular MRI: what radiologists should know - Duarte, R. (2012)
Abstract Diastolic dysfunction is a common entity and the predominant cause of heart failure in 40%-50% of patients. Diagnosis of diastolic dysfunction is clinically relevant and is associated with a poor prognosis. The aim of this essay was to review the pathophysiology and different grades of diastolic dysfunction and to provide an overview on the role of cardiovascular magnetic resonance imaging in the assessment of diastolic function.